2019
DOI: 10.1177/2325967118825473
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Risk Factors for Revision Open and Arthroscopic Proximal Biceps Tenodesis

Abstract: Background:Biceps tenodesis may be performed for symptomatic tendinopathy or tearing of the long head of the biceps tendon. Biceps tenodesis is also commonly performed as an adjunctive procedure. However, the indications and prevalence of biceps tenodesis have expanded.Purpose:To establish the incidence and risk factors for revision biceps tenodesis.Study Design:Case-control study; Level of evidence, 2.Methods:The PearlDiver database of Humana patient data was queried for patients undergoing arthroscopic or op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…54 Surgical options include biceps tenotomy or tenodesis; however, considerable debate remains regarding the optimal surgical strategy. 19,30,55,56 Both strategies provide strong clinical outcomes, however, tenotomy has less associated surgical morbidity and tenodesis may provide better maintenance of supination strength. 56 In the context of rotator cuff repairs, biceps tenotomy or tenodesis may further relieve pain and increase shoulder function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Surgical options include biceps tenotomy or tenodesis; however, considerable debate remains regarding the optimal surgical strategy. 19,30,55,56 Both strategies provide strong clinical outcomes, however, tenotomy has less associated surgical morbidity and tenodesis may provide better maintenance of supination strength. 56 In the context of rotator cuff repairs, biceps tenotomy or tenodesis may further relieve pain and increase shoulder function.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] Although functional and clinical outcomes following BT with or without RCR repair are favorable, 24,[27][28][29] concerns remain about the cost effectiveness of BT over the long-term. Arthroscopic BT has been shown to have increased costs when compared with open procedures, 30 but few data exist regarding the cost-effectiveness of arthroscopic BT alone or in combination with acro when examining total procedural and postoperative costs.…”
mentioning
confidence: 99%
“…Prior studies have suggested that the transverse humeral ligament is a distinct structure covering the intertubercular groove, which is composed of the fibers of the subscapularis tendon, with contributions from the supraspinatus tendon and the coracohumeral ligament. 24 , 25 , 26 , 27 There may be concern about the risk of subscapularis tendon damage after transverse humeral ligament release. However, this procedure has been widely used in LHBT tenodesis with excellent clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this procedure has been widely used in LHBT tenodesis with excellent clinical outcomes. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the long head of the biceps tendon (LHBT) are among the most common causes of shoulder disorders and pain (1,2). LHBT lesions alone are relatively rare; they are mostly associated with other lesions of the shoulder joint, particularly rotator cuff (RC) injury (1,(3)(4)(5)(6)(7)(8). The normal physiological function of the LHBT depends on the role of the block system, which is mainly composed of supraspinatus (SSP), coracohumeral ligament, superior glenohumeral ligament and subscapularis (SSC) (9).…”
Section: Introductionmentioning
confidence: 99%